Governmental Communication of Climate Change Risk and Efficacy: Moving Audiences Toward "Danger Control". - Akerlof, Karen L.; Boules, Caroline; Ban Rohring, Elizabeth; Rohring, Bill; Kappalman, Samantha (Environmental Management, 2020)
Public communication represents a vital civic function for governments developing climate policies, particularly with vulnerable communities under environmental justice mandates. In this study, three videos developed to support a state's climate change public engagement are used to evaluate how governmental communication using the frames of health, science, and local effects influences two theoretically important constructs, risk perception and collective efficacy. Vulnerable audiences differentiated by stress, perceived lack of control, and poor health demonstrate significant gains in collective efficacy relative to risk—"danger control" —after the intervention. But we find no differences between the three frames in their effects on perceptions of climate change risk and collective efficacy.